Persistent triple antiphospholipid antibody positivity as a strong risk factor of first thrombosis, in a long-term follow-up study of patients without history of thrombosis or obstetrical morbidity. (February 2017) - Yelnik, C M; Urbanski, G; Drumez, E; Sobanski, V; Maillard, H; Lanteri, A; Morell-Dubois, S; Caron, C; Dubucquoi, S; Launay, D; Duhamel, A; Hachulla, E; et al.
Introduction: The long-term risk of first thrombosis and benefit of prophylaxis in antiphospholipid antibody (aPL) carriers without history of thrombosis or obstetrical morbidity is poorly known. This study aimed to evaluate the long-term rate and risk factors associated with a first thrombosis in those patients. Patients and methods: After a prior study ended in December 2005 and was already published, we extended the follow-up period of our cohort of aPL carriers. Results: Ninety-eight of the 103 patients of the previous study were included. The annual first thrombosis rate was 2.3% per patient-year during a median of 13 years (6–17). None of the baseline characteristics was predictive of risk of first thrombosis, but persistent aPL over time were associated with an increased risk. The stronger association was found in triple aPL-positive carriers: OR 3.38 (95% CI: 1.24–9.22). Of note, conversely to our previous findings, no benefit of aspirin prophylaxis was observed. Conclusion: The risk of first thrombosis in aPL carriers without history of thrombosis or obstetrical morbidity was significant, persisted linearly over time and was associated with persistent aPL. This risk was especially increased in triple aPL-positive carriers, in whom a close follow-up seems to be necessary. Nevertheless, the benefit of aspirin prophylaxis remained unclear.